ASSESSMENT OF THE NON-LINGUISTIC UNIVERSITIES STUDENTS’ READINESS TO BLENDED AND E-LEARNING OF FOREIGN LANGUAGES ON THE QUESTIONNAIRE BASIS - E. V. Zubareva (Вестник университета)
The article carries out social survey analysis in the social environment of non-linguistic students of higher institution on the problems that arise when using blended and e-learning formats for foreign language acquisition. The paper lists the most popular online resources for extracurricular foreign language acquisition. Based on the results of the survey, the author concludes that the blended format of foreign language acquisition for non-linguistic students should be firmly integrated into the higher education system along with the classroom format. The study has confirmed the need to use the blended format for foreign language acquisition as the mostoptimal format of training in non-linguistic universities for both students and teachers. The research materials will be interesting to manufacturers of applications for foreign languages learning, websites that promote electronic learning of foreign languages, employees of the Ministry of Science and Higher Education of the Russian Federation, and other researchers and teachers.